Sex-specific prediction of cardiogenic shock after acute coronary syndromes: the SEX-SHOCK score : fasttrack : clinical research : acute cardiovascular care - Wang, Yifan; Zeller, Marianne; Auffret, Vincent; Georgiopoulos, Georgios; Räber, Lorenz; Roffi, Marco; Templin, Christian; Muller, Olivier; Liberale, Luca; Ministrini, Stefano; Stamatelopoulos, Kimon; Stellos, Konstantinos; et al. (European heart journal, 2024)
Cardiogenic shock (CS) remains the primary cause of in-hospital death after acute coronary syndromes (ACS), with its plateauing mortality rates approaching 50%. To test novel interventions, personalized risk prediction is essential. The ORBI (Observatoire Régional Breton sur l’Infarctus) score represents the first-of-its-kind risk score to predict in-hospital CS in ACS patients undergoing percutaneous coronary intervention (PCI). However, its sex-specific performance remains unknown, and refined risk prediction strategies are warranted.This multinational study included a total of 53 537 ACS patients without CS on admission undergoing PCI. Following sex-specific evaluation of ORBI, regression and machine-learning models were used for variable selection and risk prediction. By combining best-performing models with highest-ranked predictors, SEX-SHOCK was developed, and internally and externally validated.The ORBI score showed lower discriminative performance for the prediction of CS in females than males in Swiss (area under the receiver operating characteristic curve [95% confidence interval]: 0.78 [0.76-0.81] vs. 0.81 [0.79-0.83]; P =.048) and French ACS patients (0.77 [0.74-0.81] vs. 0.84 [0.81-0.86]; P = .002). The newly developed SEX-SHOCK score, now incorporating ST-segment elevation, creatinine, C-reactive protein, and left ventricular ejection fraction, outperformed ORBI in both sexes (females: 0.81 [0.78-0.83]; males: 0.83 [0.82-0.85]; P < .001), which prevailed following internal and external validation in RICO (females: 0.82 [0.79-0.85]; males: 0.88 [0.86-0.89]; P < .001) and SPUM-ACS (females: 0.83 [0.77-0.90], P = .004; males: 0.83 [0.80-0.87], P = .001).The ORBI score showed modest sex-specific performance. The novel SEX-SHOCK score provides superior performance in females and males across the entire spectrum of ACS, thus providing a basis for future interventional trials and contemporary ACS management.
Online veröffentlicht: 01. September 2024
Gesehen am 27.01.2025